Nutrient content and uptake by galangal (Kaempferia galanga L.) as influenced by agronomic practices as intercrop in coconut (Cocos nucifera L.) garden - Hegde, C C Biddappa, H P Maheswarappa, H V Nanjappa, M R (Journal of Spices and Aromatic Crops, 2000)
Field experiments conducted at Kasaragod, India, to study the influence of agronomic practices on galangal (Kaempferia galanga) grown as intercrop in coconut (Cocos nucifera) garden revealed that nutrient content did not differ significantly due to different types of planting material or plant population levels. Farm yard manure alone, vermicompost alone and farm yard manure and major nutrient combinations had higher nutrient contents. Nutrient uptake with mother rhizome treatment was significantly higher compared to finger rhizome. Population level of 5,00,000 plants per ha removed more nutrients. Farm yard manure alone, vermicompost application alone and farm yard manure and major nutrient combinations removed higher nutrients. Fresh rhizome yield was significanlty higher with mother rhizome and 5,00,000 population leveL Farm yard manure in combination with major nutrients recorded significantly higher fresh rhizome yield.